Honey and papaya extract loaded polyurethane based bio-nanofibrous scafford for skin regeneration - Jaganathan, S. K. (National Laboratory Astana, NAZARBAYEV UNIVERSITY, 2016)
Skin regeneration is vital for chronic or acute wounds healing. Honey and Carica papaya fruit extract are rich source of various proteins, amino acids, vitamins and essential minerals. These naturally available biomolecules have proven antioxidant, antimicrobial, anti-inflammatory, anti-scarring and healing properties. The advent of electrospinning technique has provided a platform for the synthesis of various advanced scaffolds with natural substances for effective skin regeneration.
Keywords: Honey; papaya; skin regeneration; electrospinning